Routes of TBT uptake in the clam Ruditapes decussatus. I. Water and sediments as vectors of TBT uptake - Coelho, Márcio; Bebianno, Maria João; Langston, W. J. (Marine Environmental Research, 2002)
This study assesses the relative importance of water and sediments as vectors of TBT uptake in the sediment-dwelling suspension feeder, Ruditapes decussatus. Accumulation of TBT was determined in R, decussatus exposed for 60 days to moderately high but environmentally realistic levels of TBT in water (100 ng Snl(-1)) and sediments (0.8 mug Sn g(-1) dw), separately or in combination, using constant-flow systems. The results indicate that this species accumulates TBT predominantly from water. Although some accumulation from sediments does occur. the processing of large amounts of water needed to sustain the filter-feeding habits of this species is a prime determinant of TBT uptake. The route of exposure is reflected in tissue distributions of TBT in R. decussatus. However, gills are the most important site for accumulation of TBT from water. irrespective of whether contaminated sediments are present or not. PRAXIS/BD/1424/91-IG info:eu-repo/semantics/publishedVersion